Population and mobility in the Portuguese islands: Trends from 2001 to 2021 - Gomes, C. S; Pimentel, D.; Oliveira, I.; Matos, P. T. de (Espace populations sociétés, 2024)
The aim of this paper is to analyse the demographic and migratory dynamics in the Portuguese island regions of Madeira and the Azores over the last two decades. The article begins with a brief overview of the historical and geographical context, which is essential for understanding the factors that shape population evolution and are reflected in the current situation. Beyond physical constraints such as insularity, it is important to highlight the significant historical influence of emigration in these regions and its relationship with the development of the islands over time. There have been significant changes in population growth patterns from 2001 to 2021, with a decrease in natural growth and an increased importance of migration for demographic evolution. In particular, emigration emerges as a response to economic vulnerability, playing a crucial role in moments of crisis, such as the recession of 2011-2013. Traditionally areas of emigration, the islands have experienced an increase in the proportion of foreign population, a phenomenon that reflects changes in migratory trends, particularly in Madeira, which receives a significant proportion of people from abroad. From a demographic point of view, the islands face the challenge of an ageing population, although they still have a younger demographic structure than the mainland. However, despite these changes, vulnerability persists, as reflected in indicators such as life expectancy. ***************************************************************************************************************************** L'objectif de cet article est d'analyser les dynamiques démographiques et migratoires dans les régions insulaires portugaises de Madère et des Açores au cours des deux dernières décennies. L'article commence par un bref aperçu du contexte géographique, essentiel pour comprendre les facteurs qui façonnent l'évolution de la population et se reflètent dans la situation actuelle. Au-delà des contraintes physiques telles que l'insularité, il est important de souligner l'influence historique significative de l'émigration dans ces régions et sa relation avec le développement des îles au fil du temps. Au cours de la période analysée, de 2001 à 2021, on observe des changements significatifs dans les schémas de croissance de la population, avec une diminution de l'intensité de l'accroissement naturel et une augmentation de l'importance de la migration dans l'évolution démographique. En particulier, l'émigration apparaît comme une réponse à la vulnérabilité économique, jouant un rôle crucial dans les moments de crise, comme la récession de 2011-2013. Traditionnellement zones d'émigration, les îles ont connu une augmentation de la proportion de population étrangère, un phénomène qui reflète les changements dans les tendances migratoires, en particulier à Madère, qui accueille une proportion importante de personnes venant de l'étranger. D'un point de vue démographique, les îles sont confrontées au défi du vieillissement de la population, bien qu'elles aient encore une structure démographique plus jeune que celle du continent. Cependant, malgré ces changements, la vulnérabilité persiste, comme en témoignent des indicateurs tels que l'espérance de vie.